A change in the deformation mechanism with a monotonous change of the load parameter. (December 2020) - Cherniavsky, A.O.; Cherniavsky, O.F.
Abstract: This work analyses the deformation of high-loaded structures for problems of strength and safety. Determining the load safety factor typically requires a series of calculations with successively increasing loads, up to fracture. In cyclic loading, each calculation is a numerical modeling of the structure behavior during several (or several tens) cycles up to stabilization to estimate the damage accumulated during one stable cycle. In multi-parameter loading, different load combinations may cause different mechanisms of structural deformation (i.e., different distributions of plastic strains and their velocities in the structure) with different consequences for the structure, thereby requiring different safety factors. At one-parameter loading, the assumption that the deformation mechanism remains the same for different load levels could reduce the required number of calculations. This article presents examples proving that this assumption could lead to incorrect results and requires careful verification. Highlights: Two qualitative factors characterize cyclic inelastic deformation: the type and the mechanism. The type depends on strain span and strain increment per cycle (alternating flow, strain accumulation, or their combination). The mechanism is inelastic strain rate distribution in every moment of the cycle. Different types and mechanisms lead to dissimilar consequences, which influence the estimation of strength and durability. The type and mechanism of deformation may vary with load, even for one-parameter loads.